Phenotypic analysis of sorghum [Sorghum bicolor (L) Moench] genotypes for drought responsive traits - Atnafu Kebede; Geleta Dugassa Barka; Mulugeta Kebede; Temesgen Matiwos Menamo; Taye Tadesse (Cogent Food & Agriculture)
Sorghum (Sorghum bicolor L.) production in Ethiopia is often affected by a range of abiotic factors, mainly drought. This study aimed to evaluate the genetic variation and heritability of shoot and root traits that contribute to drought tolerance in sorghum genotypes. A total of 158 genotypes were analyzed using a high-throughput phenotyping platform. Highly significant (p < .001) variations were observed for all traits considered, with strong and positive correlations among root-related traits at p < .001 (r = 0.76–0.99) and shoot traits at p < .001 (r = 0.27–0.98). The observed range of the root angles varied from 7.75° to 25.17°, with an average of 14.81°. The heritability estimates ranged from 35.51% to 76.25%, with an average of 62.40%. At an eigenvalue of greater than 1, four principal components explained 87.20% of the variability of the data sets, with PC1 and PC2 accounting for 38.10% and 34.10% of the total variability. Cluster analysis grouped the genotypes into four genetic groups. We believe that this study provides valuable insights into the genetic diversity and heritability of root and shoot-related traits in sorghum. In addition, these findings can assist in decision-making regarding the prioritization of sorghum genotypes in breeding programs targeting drought.